Coupling Reaction of Enol Derivatives with Silyl Ketene Acetals Catalyzed by Gallium Trihalides. Issue 33 (11th July 2016) - Nishimoto, Yoshihiro; Kita, Yuji; Ueda, Hiroki; Imaoka, Hiroto; Chiba, Kouji; Yasuda, Makoto; Baba, Akio
Abstract: A cross‐coupling reaction between enol derivatives and silyl ketene acetals catalyzed by GaBr3 took place to give the corresponding α‐alkenyl esters. GaBr3 showed the most effective catalytic ability, whereas other metal salts such as BF3 ⋅OEt2, AlCl3, PdCl2, and lanthanide triflates were not effective. Various types of enol ethers and vinyl carboxylates as enol derivatives are amenable to this coupling. The scope of the reaction with silyl ketene acetals was also broad. We successfully observed an alkylgallium intermediate by using NMR spectroscopy, suggesting a mechanism involving anti ‐carbogallation among GaBr3, an enol derivative, and a silyl ketene acetal, followed by syn ‐β‐alkoxy elimination from the alkylgallium. Based on kinetic studies, the turnover‐limiting step of the reaction using a vinyl ether and a vinyl carboxylate involved syn ‐β‐alkoxy elimination and anti ‐carbogallation, respectively. Therefore, the leaving group had a significant effect on the progress of the reaction. Theoretical calculations analysis suggest that the moderate Lewis acidity of gallium would contribute to a flexible conformational change of the alkylgallium intermediate and to the cleavage of the carbon−oxygen bond in the β‐alkoxy elimination process, which is the turnover‐limiting step in the reaction between a vinyl ether and a silyl ketene acetal. Abstract : Coupling with gallium : A cross‐coupling reaction between enol derivatives and silyl ketene acetals catalyzed by GaBr3 took place to give the corresponding α‐alkenyl esters (see scheme). Various types of enol ethers and vinyl carboxylates as enol derivatives are amenable to this coupling. The scope of the reaction with respect to silyl ketene acetals was also broad. A mechanism is proposed involving anti ‐carbogallation among GaBr3, an enol derivative, and a silyl ketene acetal followed by syn ‐β‐alkoxy elimination from the alkylgallium.